An E-Government Opportunity: Implications for the African Poor and Vulnerable Groups - Mosehlana, M. B. (International Conference on Public Administration and Development Alternatives (IPADA), 2019)
Information and Communication Technology (ICT) is viewed as an enabler for efficient and effective government processes, operations, interactions, service, and for accountable and transparent government i.e. a phenomenon well known as e-government. E-government is believed to present an enormous potential in innovating and transforming the manner in which government services are delivered. The potential of e-government is however challenged in the developing countries particularly in Africa due to a mist of challenges encountered in implementation. One of the prevailing arguments is that instead of expanding access to the poor and marginalized groups in the society, e-government tends to expand the gap that already exist between the rich and the poor. This paper aims to solicit African governments to prioritise e-government services targeted to the most vulnerable, marginalised, disadvantaged groups, the poor and those in the remote rural areas of the society for inclusive service delivery. The paper adopts a conceptual approach and analyses existing literature aided by scientifically published documents and reports on the subject. This methodological approach let to the determination of a variety of ICT channels which the researcher believes present a necessary potential for the poor, vulnerable groups and people in the rural areas to benefit from e-government services within the realistic context of socio-economic and material conditions encountered in the African continent. If such channels are identified, carefully managed and equipped with services that are relevant to the needs of these groups, the e-government potential can be realised to benefit the poor and vulnerable in Africa
Article published in the 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Developing countries; E-government; Rural areas; Vulnerable groups; Public administration-Technological innovations; Poor--Africa; Internet in public administration--Africa